If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(3+2x)-5(x-4)=0
We add all the numbers together, and all the variables
5(2x+3)-5(x-4)=0
We multiply parentheses
10x-5x+15+20=0
We add all the numbers together, and all the variables
5x+35=0
We move all terms containing x to the left, all other terms to the right
5x=-35
x=-35/5
x=-7
| -.75(x+)=6 | | 9c+4=3-8 | | 1.5(0.8x+0.7)-0.23=12.82 | | X2-x=5x+16 | | 3.7x+1225=13.69+35x | | 200+10x=400 | | -1/4+x=7/8 | | -2/3x-18=12 | | 1/3(2x+7)=-12 | | 2+a=7 | | 7.3y-5.18=-51.9+5.18 | | 5b-20+-3b=50 | | 20-5n=0 | | 3x+(-4)=21 | | .9(.6x-1.2)+.37=-43.91 | | 7p-4p-p=-9-2 | | -3p^2+9000-1200000=0 | | a+49=225 | | 15+3y=A | | 2x-3=12-9 | | 11k=134 | | 5k=95 | | 7f=133 | | 6x/11+4=2×/11+16 | | 3+3(x-1)=1 | | 55-19x=2x | | -18=x-8x | | 6/11x+4=2×/11+16 | | 3/2=15/z | | (2/3+s)6=3 | | 3/4d-11=1/4d-6 | | 20x-14-11x=-8-6x |